A Metatheatrical Reading of Baroque and Neobaroque Texts: Entremés del retablo de las maravillas (1615) and De donde son los cantantes (1967). Issue 4 (2nd October 2019) - Zhang, Yunning
Abstract: This article examines the diachronic use of metatheater in Cervantes's Entremés del retablo de las maravillas (1615) and "La Dolores Rondón, " the second tale in Severo Sarduy's novel, De donde son los cantantes (1967). Both works are structured as a play-with-in-a-play, including the internal theatrical pieces and the external debates, where the authors problematize literary language/representation in their respective times. This article further explores the organizational differences between metatheatrical Baroque and Neobaroque texts. In the Entremés, two charlatans trick a group of villagers fearful of the "limpieza de sangre" into seeing marvelous scenes. This Baroque play suggests the omnipresence of the Spanish Empire, while criticizing the trendy performance of comedia nueva in Cervantes's time. "La Dolores Rondón, " by comparison, fails to deliver a coherent piece of theater. Following the tradition of the Cuban "choteo, " the characters humorously demonstrate that all "realities" are fictional and that the text progresses without the guidance of chronological or poetic order. Sarduy's Neobaroque narrative seeks to break away from authoritative literary discourse and to repudiate the logocentrism embedded in Latin American epistemology.